2009
DOI: 10.3366/ijhac.2009.0010
|View full text |Cite
|
Sign up to set email alerts
|

Prehistoric resource procurement in the central Mesa Verde region: A study of human mobility and social interactions using GIS

Abstract: The use of a Geographic Information System (GIS) in the study of lithic procurement patterns provides crucial information about energy expenditure and territoriality of prehistoric communities. Cost-weight analyses calculate proxy energetic expenditures of agents who transport lithic materials from a quarry to the nearest habitation site. Illustrating energy expenditure values onto maps helps us understand changes in toolstone procurement patterns through time. Comparing energy expenditure values from one time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…As summarized by Arakawa and Nicholson (2010), ethnographic studies suggest that the daily activities of sedentary agriculturalists tend to be concentrated in a primary area within 1-2 km of the residence that encompasses principal water sources and most agricultural fields. A secondary exploitation area then extends outward to 5-10 km from the residence where most of the hunting and fuel wood collection is done, and beyond it is a non-exploitive zone where other materials including lithic and clay sources may be located.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized by Arakawa and Nicholson (2010), ethnographic studies suggest that the daily activities of sedentary agriculturalists tend to be concentrated in a primary area within 1-2 km of the residence that encompasses principal water sources and most agricultural fields. A secondary exploitation area then extends outward to 5-10 km from the residence where most of the hunting and fuel wood collection is done, and beyond it is a non-exploitive zone where other materials including lithic and clay sources may be located.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Distances to source areas and assemblage proportions are the primary data that are used to conduct this analysis. Arakawa and Nicholson (2010) effectively employed minimum-energy pathways (which take into account the differences in energy expended in traversing varying terrain) in their analysis of lithic procurement patterns and territoriality in the central Mesa Verde region. We opted to use simple straight-line distances in part because this was a preliminary study but mainly because the lithic procurement behaviors of mobile hunter-gatherers are fundamentally different from that of the sedentary agriculturalists.…”
Section: Procurement Strategy Analysismentioning
confidence: 99%
“…Possibilities of interdisciplinary researches, multifunctionality of GIS attract the increasing number of historians. Researches, connected with the spatial analysis (in Russia, as well as abroad) are conducted in two directions: 1) theoretical, in the frames of which the GIS use bases are specified and adjusted in the history research (Owens, 2008;Gregory & Cooper, 2009;Igonin, 2011;Knowles, 2013) and 2) practical, when authors describe their own experience and specific cases of GIS application, problems they faced during research, and the way of their solution (Raymond, 2011;Boeckel & Otterstrom, 2009;Arakawa & Nicholson, 2010;Rygalova & Chibisov, 2012). In 1960s large data files were processed by means of the electronic computer machine and at the boundary of 1980 and 1990 successful attempts "to refer" data of demographic character to the area were made in the USA and Canada.…”
Section: Relevance Of the Problemmentioning
confidence: 99%
“…Brantingham's (2003) study successfully reproduced patterns in raw material richness qualitatively similar to those commonly observed in the historical record (Cegielski & Rogers, 2016). Arakawa and Nicholson's (2009) study indicated that increase in population size during the Pueblo III period in the central Mesa Verde region required more energy when searching for lithic materials for tool making, thus leading to communities that were more aggregated during the later period relying on lower quality raw materials. Barceló et al's (2015) model provided insight into how people modified their traditional residential mobility and dispersal patterns, within the context of social complexity (wars, conflicts, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Other archeological studies have used ABMs to simulate the procurement of raw material (i.e., stone) (Arakawa & Nicholson, 2009; Brantingham, 2003), as well as the emergence of race and territory in Patagonia (Barceló et al, 2015). Brantingham's (2003) study successfully reproduced patterns in raw material richness qualitatively similar to those commonly observed in the historical record (Cegielski & Rogers, 2016).…”
Section: Introductionmentioning
confidence: 99%